COMPLEX CRITERIA FOR ESTIMATION OF THERMAL POWER STATION OPERATIONAL EFFICIENCY - S. N. Shychko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2005)
The operational analysis of a generating set has been carried out in view of profitability, reliability and environmental factor indices. The generalized function of usefulness describing efficiency level of the generating set has been obtained.